The Covid-19 Pandemic—Opportunities for Circular Economy Practices Among Sewing Professionals in the City of Curitiba-Brazil - Corrêa, Harrison Lourenço; Corrêa, Daniela Gallon (Frontiers in Sustainability, 2021)
The pandemic that the world has been facing since Jan-2020 has promoted rapid changes in the form of consumption and service provision. In many countries, GDP forecasts have turned negative. But, if on the one hand, the prospects were negative, on the other, there were positive signs, including the adoption of recycling, remanufacturing, and reuse practices. Reusing raw materials in their production lines, companies and volunteers produced masks for mandatory use by the population of some countries such as Brazil. This brief period energized an economy that until then seemed to be dormant. In view of this scenario that took shape in the world, the present study aimed to assess how this pandemic affected sewing professionals' enterprises, contributing to an income generation and to a possible sustainable practice. The level of circularity was evaluated through a questionnaire and interviews as it was impossible to visit the ateliers. The survey of enterprise circularity was based on basic principles of circular economy from Ellen MacArthur Foundation. The questions were made considering some features, like level of knowledge about the theme The prospecting of the potential interviewers was carried out through a digital platform in the month of September-2020. Results obtained by fabric remnants mass balance indicated some level of circularity in the production mode of seamstresses during the pandemic. The challenge, however, is the high demand for masks allied to the search for customization by consumers. This represents the main obstacles to maintaining circularity in the production process.